The institutionalization of organizational ethics - Sims, Ronald R. (Journal of business ethics, 1991)
The institutionalization of ethics is an important task for today's organizations if they are to effectively counteract the increasingly frequent occurrences of blatantly unethical and often illegal behavior within large and often highly respected organizations. This article discusses the importance of institutionalizing organizational ethics and emphasizes the importance of several variables (psychological contract, organizational commitment, and an ethically-oriented culture) to the institutionalization of ethics within any organization., ... institutionalizing ethics may sound ponderous, but its meaning is straightforward. It means getting ethics formally and explicitly into daily business life. It means getting ethics into company policy formation at the board and top management levels and through a formal code, getting ethics into all daily decision making and work practices down the line, at all levels of employment. It means grafting a new branch on the corporate decision tree — a branch that reads “right/wrong” (Purcell and Weber, 1979, p. 6).